2021
DOI: 10.1002/pbc.28903
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Waldeyer's ring in pediatric and adolescent Hodgkin lymphoma patients—Importance of multimodality imaging: Results from the EuroNet‐PHL‐C1 trial

Abstract: Background In the EuroNet Pediatric Hodgkin Lymphoma (EuroNet‐PHL) trials, decision on Waldeyer's ring (WR) involvement is usually based on clinical assessment, that is, physical examination and/or nasopharyngoscopy. However, clinical assessment only evaluates mucosal surface and is prone to interobserver variability. Modern cross‐sectional imaging technology may provide valuable information beyond mucosal surface, which may lead to a more accurate WR staging. Patients, materials, and methods The EuroNet‐PHL‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In our recent publication entitled "Assessment of Waldeyer's ring in pediatric and adolescent Hodgkin lymphoma patients-Importance of multimodality imaging: Results from the EuroNet-PHL-C1 trial," we showed that Waldeyer's ring (WR) involvement in pediatric Hodgkin lymphoma (HL) is rare, and that the diagnosis is easily made by applying an image-based algorithm, which considers information from morphologic and metabolic cross-sectional imaging. 1 The only weakness of this publication was that we could not substantiate our results by additional histopathological information, as in none of the analyzed subjects the WR was biopsied. 1 As a complement, we now present the case of a 16-year-old male pediatric HL patient whose WR involvement was confirmed through multidisciplinary involvement, and in whom biopsy delivered important information explaining why the diagnosis of WR involvement was made with a significant delay.…”
Section: E T T E R T O T H E E D I T O R Waldeyer's Ring Involvement ...mentioning
confidence: 89%
See 1 more Smart Citation
“…In our recent publication entitled "Assessment of Waldeyer's ring in pediatric and adolescent Hodgkin lymphoma patients-Importance of multimodality imaging: Results from the EuroNet-PHL-C1 trial," we showed that Waldeyer's ring (WR) involvement in pediatric Hodgkin lymphoma (HL) is rare, and that the diagnosis is easily made by applying an image-based algorithm, which considers information from morphologic and metabolic cross-sectional imaging. 1 The only weakness of this publication was that we could not substantiate our results by additional histopathological information, as in none of the analyzed subjects the WR was biopsied. 1 As a complement, we now present the case of a 16-year-old male pediatric HL patient whose WR involvement was confirmed through multidisciplinary involvement, and in whom biopsy delivered important information explaining why the diagnosis of WR involvement was made with a significant delay.…”
Section: E T T E R T O T H E E D I T O R Waldeyer's Ring Involvement ...mentioning
confidence: 89%
“…1 The only weakness of this publication was that we could not substantiate our results by additional histopathological information, as in none of the analyzed subjects the WR was biopsied. 1 As a complement, we now present the case of a 16-year-old male pediatric HL patient whose WR involvement was confirmed through multidisciplinary involvement, and in whom biopsy delivered important information explaining why the diagnosis of WR involvement was made with a significant delay. This patient presented in May 2020 to an outpatient ear-nosethroat (ENT) specialist because of prolonged nasal obstruction.…”
Section: E T T E R T O T H E E D I T O R Waldeyer's Ring Involvement ...mentioning
confidence: 89%
“…In all patients with LR, an additional PET and morphological assessment of the thymus was re‐evaluated in consensus by a radiologist (Dietrich Stoevesandt) and a nuclear physician (Lars Kurch), both experienced in the evaluation of pediatric HL. Thymic LR was defined as a positive biopsy with proof of CHL together with one or more focal FDG uptakes in the thymus that exceeded that of the liver 24,34 . The additional reassessment of the thymic region was done to rule out an alternative explanation for the increased PET uptake.…”
Section: Methodsmentioning
confidence: 99%
“…Positron emission tomography CT (PET‐CT) was also able to distinguish between tumor entities using standardized uptake value (SUV) cutoffs 15 . HL lesions are regularly of focal and not diffuse appearance in fluorodeoxyglucose ( 18 F‐FDG)‐PET 24,25 . In MRI, chemical‐shift imaging can be used for interpretation, although certain overlap exists in early adulthood 26 …”
Section: Introductionmentioning
confidence: 99%
“…Recent chemotherapy reduces the patient's immunity further, which increases the risk for infections [5]. The use of 2-[ 18 F]FDG PET/CT in combination with MRI is useful to identify pathology in Waldeyer's ring [7].…”
Section: Paediatric Lymphomamentioning
confidence: 99%